Global Tuberculosis Report 2020 – Reflections on the Global TB burden, treatment and prevention efforts - Chakaya, Jeremiah; Khan, Mishal; Ntoumi, Francine; Aklillu, Eleni; Fatima, Razia; Mwaba, Peter; Kapata, Nathan; Mfinanga, Sayoki; Hasnain, Seyed Ehtesham; Katoto, Patrick D.M.C.; Bulabula, André N.H.; Sam-Agudu, Nadia A.; et al. (International journal of infectious diseases, 2021)
•In 2020, COVID-19 dislodged TB as the top infectious disease cause of mortality globally.•Globally, an estimated 10.0 million people developed active TB disease in 2019, with 1.4 million TB deaths.•The WHO regions of South-East Asia, Africa, and the Western Pacific had the most cases of TB.•Progress in achieving the United Nations (UN) General Assembly End TB targets remains slow.•TB services need to be ramped up, and underlying drivers of TB need be addressed. The October 2020 Global TB report reviews TB control strategies and United Nations (UN) targets set in the political declaration at the September 2018 UN General Assembly high-level meeting on TB held in New York. Progress in TB care and prevention has been very slow. In 2019, TB remained the most common cause of death from a single infectious pathogen. Globally, an estimated 10.0 million people developed TB disease in 2019, and there were an estimated 1.2 million TB deaths among HIV-negative people and an additional 208, 000 deaths among people living with HIV. Adults accounted for 88% and children for 12% of people with TB. The WHO regions of South-East Asia (44%), Africa (25%), and the Western Pacific (18%) had the most people with TB. Eight countries accounted for two thirds of the global total: India (26%), Indonesia (8.5%), China (8.4%), the Philippines (6.0%), Pakistan (5.7%), Nigeria (4.4%), Bangladesh (3.6%) and South Africa (3.6%). Only 30% of the 3.5 million five-year target for children treated for TB was met. Major advances have been development of new all oral regimens for MDRTB and new regimens for preventive therapy. In 2020, the COVID-19 pandemic dislodged TB from the top infectious disease cause of mortality globally. Notably, global TB control efforts were not on track even before the advent of the COVID-19 pandemic. Many challenges remain to improve sub-optimal TB treatment and prevention services. Tuberculosis screening and diagnostic test services need to be ramped up. The major drivers of TB remain undernutrition, poverty, diabetes, tobacco smoking, and household air pollution and these need be addressed to achieve the WHO 2035 TB care and prevention targets. National programs need to include interventions for post-tuberculosis holistic wellbeing. From first detection of COVID-19 global coordination and political will with huge financial investments have led to the development of effective vaccines against SARS-CoV2 infection. The world now needs to similarly focus on development of new vaccines for TB utilizing new technological methods.